A decentralized call recording in voice over IP based on blockchain using smart contracts - Abdelhadi Rachad; Lotfi Gaiz; Khalid Bouragba; Mohammed Ouzzif (Institute of Advanced Engineering and Science, 2026)
Although voice over IP (VoIP) has established itself as the new paradigm for universal telecommunications, its massive deployment within businesses and government agencies has paradoxically increased the attack surface for cyber threats: stream injection fraud, identity theft, and, more recently, the emergence of voice deepfakes, rendering traditional security architectures obsolete. At the same time, conventional centralized recording systems raise trust issues, as they are vulnerable to data manipulation, unauthorized access, and single points of failure. This article presents a new architecture that decentralizes the recording and securing of VoIP calls by combining three key technologies: blockchain for immutability; smart contracts to automate communications governance and ensure the transition from a centralized to an algorithmic trust model; and artificial intelligence (AI) agents that analyze audio streams in real time. This approach transforms VoIP recording from a simple passive file into a secure, auditable, and confidential digital asset. By removing centralized control and strengthening identity verification, this architecture provides a concrete response to security requirements.